Edukasi Pencegahan Serangan Stroke Pada Ibu Rumah Tangga Dengan Pengendalian Faktor Resiko Stroke Di Kel. Balleangi Kec. Balocci Kab. Pangkep - Salaman Alhidayat, Nurun; Esti Handayani, Dwi; Zakariyati, Zakariyati; Halimah, Nur (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2024)
The incidence of stroke increases with age, with an estimated 10% of ischemic strokes occurring in individuals under 50 years of age. Stroke itself has consequences that can worsen a person's condition both physically and psychologically, especially in young adults. The method implemented to help the community is by providing counseling and assistance to housewives. The counseling provided using the SUPERNOL method is Spiritual, Management of Feelings, Using Ratios, Nutrition and Exercise. The results of the service show that participants are able to know and understand preventing recurrent strokes and controlling stroke risk factors.